C# program verification problems: solution by a three-level method - Promsky, A.V. (Інститут програмних систем НАН України, 2008)
The evolution of formal methods allowed us to overcome many obstacles in verification of procedural programs. However, wide spreading of object-oriented languages has brought new challenges, even in the case of sequential programs. These problems were thoroughly exam-ined by ESC/Java and Spec#, though in many cases they just state the presence of the challenge. This paper presents an overview of some problematic issues and a three-level approach to their solution in the C#-light project.